(untitled) (University of Khartoum Engineering Journal, 2022)
Orthogonal Frequency Division Multiplexing (OFDM) has become the modulation technique used inseveral present and future communication standards. It is tolerant to frequency selective channels and provides high data rates. In this paper we investigate the theory and challenges of OFDM. A mathematical model is derived and used to explain the principles of OFDM. The model is then used to investigate inter-carrier interference (ICI) in OFDM systems. BER expressions are then derived and used to analyze the performance of OFDM systems withmobility.